A novel anxiety-associated SNP identified in LYNX2 (LYPD1) is associated with decreased protein binding to nicotinic acetylcholine receptors - Anderson, Kristin R.; Cao, Wenpeng; Lee, Hui Sun; Crenshaw, Mark A.; Palumbo, Talulla B.; Fisher-Perez, Ethan; DeGraaf, Amanda; Rogu, Peter; Beatty, Maria A.; Gracias, Gabrielle M.; Pisapati, Avani V.; Hoffman, Katie; et al. (Frontiers in Behavioral Neuroscience, 2024)
Anxiety disorders are among the most common mental illnesses in the US. An estimated 31.1% of U.S. adults experience any anxiety disorder at some time in their lives. The murine Lynx2 gene, which encodes a protein modulator of nicotinic acetylcholine receptors, is expressed within anxiety-related neural circuitry in rodents and has been functionally associated with anxiety-like behavior. Here, we investigated variation in the human LYNX2 (LYPD1) gene and the possible effects that variation has on anxiety levels in a cohort of 624 participants. Participants were given validated anxiety questionnaires (e.g. STICSA and STAI) that asked them to report both on anxiety experienced at the time of the test and on anxiety they feel they experience more generally. We found that a specific and previously unreported single nucleotide polymorphism (SNP) in the mature protein-coding region of LYNX2 was correlated with high anxiety scores. These elevated values were most similar to those of the patient population of clinically diagnosed generalized anxiety disorder and panic disorder, although this genetically defined subpopulation did not generally report such diagnoses. The LYNX2 protein has been shown to bind to multiple nicotinic acetylcholine receptor subtypes, including α4β2, α7, and α3β4 subtypes, each of which have been shown to be involved in affective behaviors. We performed computational modeling on one of these subtypes, the homopentameric α7 subtype, and in vitro atomic force microscopy (AFM) which revealed that this LYNX2 SNP is associated with a reduced binding affinity of the LYNX2/nAChR interaction, providing a possible functional explanation for the role this mutation plays in Anxiety-specific LYNX2 variant modulation of anxiety. This work reveals a potential biomarker and diagnostic tool for the early detection of individuals with susceptibility to anxiety.